THE ROLE OF CT IN THE DIAGNOSIS OF ACUTE PULMONARY EMBOLISM - Nizamova Madina Mirgabtizyanovna; Yarmuchamedova Dilarom Salidjanovna; Yuldasheva Manzura Akromovna; Borodavko Tatyana Gennadyevna; Kozivko Sergey Sergeyevich (Scholar Express Journals, 2025)
A comparative analysis of two groups of patients was conducted. The first group did not show any changes in the lung parenchyma, while the second group had severe lung lesions with hemorrhages in the pulmonary alveoli and signs of pulmonary infarction. Along with the expansion of the pulmonary trunk, branches of the right and left pulmonary arteries on CT angiography, characteristic radiological signs of acute PE in the presented patients include an increase in the right and left ventricles of the heart without signs of right ventricular hypertrophy, flattening and displacement of the interventricular septum.
Keywords: pulmonary embolism; clinical observatio; visualization